The island house : a novel - Thayer, Nancy, 1943- (Ballantine Books, 2016)
"Soak up the sun with this delightful novel from New York Times bestselling author Nancy Thayer! Every summer since college, twenty-nine-year-old Courtney has traded the familiarity of the Midwest for the allure of Nantucket. Now an established university professor, she finds herself caught between two lifestyles and two very different men. Because this summer has taken an unexpected turn and now she must decide what she really wants"--